ZAHİRİLİĞİN BÜYÜK İMAMI İBN HAZM: HAYATI VE ESERLERİ - Şahabettin Ergüven (İslami İlimler Dergisi)
Ibn Hazm lived in the period of time years during the falling down of Andalus-Amawian State (765-1031). He wrote alot of of books on different fields such as Fıgh, Hadith, History of Religion, Islamic theology, Philosophy, Logic, Genealogy, Language and Literatury. More over he had systematized of the Zahiri sect in the Islamic jurisprudence. Works on Zahiri sect written by Hazm made him one of the famous person among the scholars in the world. In this article ıt is dealt with the life and Works of Ibn Hazm al-Andalusian